Neighbourhood deprivation and outlet density for tobacco, alcohol and fast food: first hints of obesogenic and addictive environments in Germany - Schneider, Sven; Gruber, Johannes (Public health nutrition, 2013)
Objective: The current discussion regarding ‘place effects on health’ is increasingly focusing on the characteristics of a specific physical environment. Our study investigated whether socially deprived residential areas are more likely than affluent neighbourhoods to provide access to addictive substances and fast food. Design: In this ecological study the total number of tobacco, alcohol and fast-food outlets was recorded and visualized using a geographic information system. Area affluence was measured through the percentage of parents with children of kindergarten or school age with joint annual taxable income <€12 272. Setting: Eighteen social areas in Cologne, Germany. Subjects: All social areas in four districts in Cologne, Germany, with a total of 92 000 inhabitants, were analysed. Results: In the investigation area, 339 tobacco, 353 alcohol and sixty-seven fast-food outlets were identified. As area affluence declined the availability of the following potentially health damaging sources increased: cigarettes (Kendall's tau = 0·433; P = 0·012), alcohol (Kendall's tau = 0·341, P = 0·049) and fast food (Kendall's tau = 0·473; P = 0·009). Conclusions: The availability of addictive substances and fast food can be seen to have a contextual influence on an individual's lifestyle and can, in the form of physical exposure to obesogenic and addictive environments, contribute to a culmination of health risks.
Published online: 10 July 2012
Gesehen am 18.06.2018